RETENSI ASAM EIKOSAPENTAENOAT (EPA) TORTILLA TEPUNG IKAN LELE SELAMA PENGOLAHAN DAN PENYIMPANAN PADA SUHU RUANG - Lutvina Vitasari; Mappiratu Mappiratu; Ni Ketut Sumarni (KOVALEN: Jurnal Riset Kimia, 2016)
A research on the retention of eicosapentaenoic acid (EPA) on theprocessing and storage of functional tortillas.This study aims to determine the retention of eicosapentaenoic acid (EPA)flour tortillas catfish during processing and storage at room temperature.The research method includes the step of making flour catfish, processing tortillas and tortilla storage at room temperature.Analysis eicosapentaenoic acid in the tortilla is done every 7 days for 56 days using Gas Chromatography.The Results obtained indicated eikosa penta enoic acid were demaged during processing tortillas with the level of demage 9,17%. Tortillas storage at room temperature for 56 days lead to demage 31,97% EPA.Keywords: Eicosapentaenoic Acid, Retention, Tortilla